Reproductive rates and milk yield of Kenana cattle in Sudan - Alim, K.A. (Cambridge University Press, 1960)
An analysis has been of the reproductive rates and milk yield of Kenana cattle in a closed dairy herd in Sudan. The average age at first calving was 38.4 months and calving were most frequent between September and December. The average length of productive herd life of cows was 5.42 lactations. The average interval between successive calvings was 395 days, and this was influenced by years and age. The mean generation interval was 6.72 years. The average milk yield in 224 days was 338 gal. With a standard deviation of 152 gal. There was a close relationship between milk yield and lactation length; r = 0.866 ± 0.013. Milk yield increased by age until the fourth lactation. The rate of increase in yield between first and second lactation was highest and amounted to 22%. Year of record had a pronounced effect on milk yield. Month of the calving had a slight effect on milk yield. The repeatability estimates of single records milk yield, calving intervals, lactation periods and dry periods were 0.432±0.046, 0.058±0.059, 0.192±0.058 and 0.069±0.065, respectively. The increase in repeatability estimates between earlier and later successive milk yield records was accompanied by a decrease in the coefficients of variation of these records. The heritability of a single record milk yield was 0.239±0.245. The rate of annual genetic superiority in milk yield of dams of cows and dams of bulls was found to be 0.74% of the herd average.